2023
DOI: 10.1002/lsm.23634
|View full text |Cite
|
Sign up to set email alerts
|

Structural design optimization and lipolytic effect prediction of vacuum suction cryolipolysis applicator: Simulation study

Abstract: Background and Objectives: Cryolipolysis is a popular noninvasive lipolytic method that uses low temperature to induce apoptosis or necrosis of adipocytes to reduce local fat in the human body. Vacuum suction applicator is a commonly used cryolipolysis equipment, which suction human skin and fat into a chamber for cooling. The structure of vacuum suction applicator is usually irregular, its cooling characteristic is also complex, and unreasonable suction structure will cause human discomfort. Biological experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Lower vacuum skin tension is more comfortable and preferred by patients. A recent simulation study found an inverse relationship between the suction angle and the cooling capacity, with smaller suction angles resulting in greater cooling capacity, as well as cooling to deeper levels of subcutaneous fat 21 . Decreasing or maximizing suction angle can also result in increased patient comfort.…”
Section: Clinical Advances and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower vacuum skin tension is more comfortable and preferred by patients. A recent simulation study found an inverse relationship between the suction angle and the cooling capacity, with smaller suction angles resulting in greater cooling capacity, as well as cooling to deeper levels of subcutaneous fat 21 . Decreasing or maximizing suction angle can also result in increased patient comfort.…”
Section: Clinical Advances and Applicationsmentioning
confidence: 99%
“…A recent simulation study found an inverse relationship between the suction angle and the cooling capacity, with smaller suction angles resulting in greater cooling capacity, as well as cooling to deeper levels of subcutaneous fat. 21 Decreasing or maximizing suction angle can also result in increased patient comfort. Emerging technologies should further explore the relationship of vacuum suction to treatment outcomes, aiming to maximize treatment comfort and efficiency.…”
Section: Novel Applicatorsmentioning
confidence: 99%